Harga Jual UMKM Tenun Sambas Naik Kelas - Aldo, Aldo; Jainal, Jainal; Aulia, Nur; Noviriani, Eliza (Sehati Abdimas, 2024)
This research aims to determine the ideal selling price of MSME products for Sambas Songket Irmawati Weaving in accordance with accounting theory. This is because most of the MSMEs of Weaving Sambas set the selling price based on estimates or according to the usual market price and the purpose of this research is to find out the potential sustainable benefits of determining the selling price of products. This study uses a descriptive research method with a quantitative approach. This type of research was chosen because it aims to provide an overview of how the full costing method in identifying production costs, namely raw material costs, direct labor costs, variable and fixed factory overhead costs to calculate the total cost of production through calculations that have been theoretically determined. The sampling technique used in this study is non-probability sampling with a purposive sampling approach. The results of the analysis on the cost of production using the full costing method calculation resulted in diversification of product selling prices that are ideal for MSMEs. The potential sustainable benefits can be formulated in increasing sales turnover, preserving Sambas Malay culture, and developing MSMEs in Sambas district.